Miss Pettigrew lives for a day [videorecording (DVD)] - Nalluri, Bharat; Adams, Amy; Alexander, David; Clifford, Clare; Watson, Winifred, 1906-2002 (Universal Studios Home Entertainment, 2008)
In 1939 London, Miss Guinevere Pettigrew is a middle-aged governess who finds herself once again unfairly dismissed from her job. Now she must seize the day if she wants a job. She does this by intercepting an employment assignment outside of her comfort level as social secretary. Arriving at a penthouse apartment for the interview, Miss Pettigrew is catapulted into the glamorous world and dizzying social whirl of an American actress and singer, Delysia Lafosse. Suddenly, Miss Pettigrew finds herself swept into the world of high society. Within hours she is living it up. Taking the social secretary designation to heart, she tries to help her new friend Delysia navigate both a love life and career. This is complicated by the three men in Delysias life: devoted pianist Michael, intimidating nightclub owner Nick, and impressionable junior impresario Phil. Miss Pettigrew herself is unexpectedly drawn to the gallant Joe, a successful designer who is tenuously engaged to haughty fashion maven Edythe - the one person who senses that the new social secretary may be out of her element and schemes to undermine her. Over the next 24 hours, Guinevere and Delysia will empower each other to discover their romantic destinies.